Factors that affect employee’s intention to stay at Syarikat Air Melaka Berhad (SAMB) / Nur Farahin Jantan - Jantan, Nur Farahin (2014)
Employee retention is very important for an organization to success and avoid high turnover rate. The purpose of this study is to observe the significant correlation relationship of the factors such as compensation and benefit, career development and supervisor support with employee’s intention to stay at SAMB and to identify the most influential factor that influences employee’s intention to stay at SAMB. The data was collected through questionnaire with a total of 144 staffs of SAMB at headquarters. This research was conducted based on simple random sampling method. Findings showed that there were significant relationships between compensation and benefit, career development, supervisor support and employee’s intention to stay at SAMB. All hypotheses were supported with the variables and failed to be rejected. This study also presents a conclusion and recommendations for manager to improve their employee’s retention strategy and to decrease employee’s turnover rate.